Emerging magnetodielectric materials for 5G communications: 18H hexaferrites. (1st June 2022) - Li, Qifan; Chen, Yajie; Yu, Chengju; Young, Lance; Spector, Jonah; Harris, Vincent G.
Abstract: With the rapid development of 5G technologies, it is crucial to seek magnetodielectric materials with high permeability and permittivity, low magnetic and dielectric losses, and high cutoff frequency over the sub-6 GHz frequency bands. Due to limited resonant frequency and large natural resonance linewidth, conventional microwave ferrites and their composites do not meet these requirements. Here, the microwave properties and their temperature dependence of a unique type of hexaferrites, Mg-Zn 18H hexaferrite (Ba5 Mg2− x Zn x Ti3 Fe12 O31 ), are reported. Polycrystalline Mg-Zn 18H hexaferrite exhibited an extremely low damping coefficients ( α = 0.1-0.2), remarkably low magnetic loss (tan δ m = 0.06), excellent thermal stability of the damping coefficient (Δ α /Δ T = 0.0004 K −1 ), and a narrow ferromagnetic resonance (FMR) linewidth (Δ H = 486–660 Oe). Moreover, Mg-Zn 18H hexaferrite possessed significant enhancement in the figure of merit (FOM = μ'Qf ) compared to conventional microwave ferrites and their composites. When employed as the substrate of a 3.6-GHz patch antenna, Mg-Zn 18H hexaferrite demonstrated significant advantages for miniaturization (∼5 ×) and bandwidth improvement (∼50–110%) over conventional dielectric substrates. These results represent the best magnetic performance among the microwave ferrites reported at the S band and reveal the great technological value and commercial potential for 5G communications. Graphical abstract: Image, graphical abstract .